EVALUATING TOUR006 IN PARTICIPANTS WITH CHRONIC KIDNEY DISEASE AND ELEVATED HS-CRP: RATIONALE AND DESIGN OF THE TRANQUILITY PHASE 2 STUDY - Emil DeGoma, MD (Elsevier, 2024)
Therapeutic Area: Pharmacologic Therapy Background: Subgroups of patients with atherosclerotic cardiovascular disease (ASCVD) remain at very high risk of major adverse cardiovascular and limb events despite lifestyle modification and intensive pharmacological management including antiplatelet drugs, antihypertensive therapy, and LDL-lowering medications. Converging evidence from human genetic studies, prospective cohort studies, and mechanistic studies as well as results of canakinumab and colchicine cardiovascular outcome trials support the therapeutic potential of IL-6 pathway inhibition to lower the risk of ASCVD independent of traditional risk factors. TOUR006 is a fully human, high-affinity monoclonal antibody against the IL-6 cytokine. In prior Phase 1/2 studies, TOUR006 administered to patients with high-grade inflammatory autoimmune diseases such as rheumatoid arthritis, Crohn's disease, and systemic lupus erythematosus achieved rapid and durable reductions in C-reactive protein (CRP), the key downstream pharmacodynamic (PD) biomarker of IL-6 activity, as assessed by the high-sensitivity (hs) assay. A pharmacokinetic (PK)/PD model was developed from these data, and simulations in virtual patients showed significant reductions in hs-CRP with both monthly and quarterly dosing of TOUR006. The objective of this Phase 2 study is to characterize the hs-CRP-lowering effect, safety, tolerability, and PK of TOUR006 in patients with chronic kidney disease (CKD) and elevated hs-CRP. The CKD population was selected for this trial because of the high prevalence of elevated hs-CRP as well as evidence supporting a significant role of IL-6 pathway activation in driving ASCVD risk among patients with CKD. Methods: TRANQUILITY is a Phase 2, randomized, double-blind, placebo-controlled, multicenter, US-based trial enrolling approximately 120 patients with CKD stage 3 or 4 and hs-CRP≥2 and <15 mg/L. Participants will be stratified by CKD stage and randomized to subcutaneous TOUR006 50 mg quarterly, 25 mg quarterly, 15 mg monthly, or placebo (Figure). The primary PD endpoint is change in hs-CRP; additional biomarkers include IL-6, lipoprotein(a), oxidized LDL, and fibrinogen. Treatment and follow-up periods are 180 days and 185 days, respectively. Conclusions: TRANQUILITY, an ongoing trial with anticipated primary completion in May 2025, will assess the safety, tolerability, PK, and hs-CRP-lowering effect of TOUR006 and inform the dosing regimen and design of future Phase 3 cardiovascular studies in high-risk patients.